Empirical Analysis of Five Child-Killer Diseases and Under Five Mortality in Adamawa State, Nigeria - Dalatu, Paul Inuwa; Ibrahim, Asabe; Kwanamu, Joshua A. (Balai Publikasi Indonesia, 2024)
Under-Five Mortality rate refers to the probability a new-born would die before reaching exactly 5 years of age, expressed per 1,000 or 100,000 live births. The Five Child-Killer Diseases used in this study are Pneumonia, Diarrhoea, Measles, Tetanus and Polio. The study used Ex post facto design with quantitative approach. A secondary data of the Five-Child Killer Diseases and Under-Five Mortality were obtained from the twenty-one (21) Local Government Primary Health Care Development Agency in Adamawa State between the periods of 2008 to 2022. The study measured the mortality rate due to the Five Child-Killer Diseases and its Cause-effect on the Overall Under-Five Mortality Irrespective of Diseases in the study area and then develop a model for future prediction. Based on the finding, the Overall Under-Five Mortality rate increases from 112 to 314 deaths per thousand live births between 2008 and 2012, followed by a sudden decrease from 261 to 90 deaths from 2013 to 2016 and then fluctuate throughout the rest of the period under review. Individually, the largest contributor of Under-Five Mortality among the Five Child-killer Diseases is Diarrhea with 89 deaths per thousand live births in 2011, followed by Measles with 39 deaths in the same year. The regression model revealed a positive and insignificant causal relationship between deaths due to Pneumonia, Diarrhoea and Measles on Overall Under-Five Mortality in the study area. The regression model also explained that; at zero deaths due to the Five Child-Killer Diseases, the Overall Under-Five Mortality is more than 105 deaths in the study area.